THE EFFECTS OF CORPORATE SOCIAL RESPONSIBILITY, BRAND REPUTATION, AND CONSUMER TRUST ON ENTREPRENEURIAL VENTURES - Jama, Ahmad Kamal (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study investigates the effects of Corporate Social Responsibility (CSR), brand reputation, and consumer trust on the performance of entrepreneurial ventures. Utilizing a quantitative approach and surveying 250 consumers who have recently interacted with entrepreneurial businesses, the research employs Structural Equation Modeling (SEM) to test hypothesized relationships. Results reveal that CSR significantly enhances brand reputation and consumer trust, with brand reputation partially mediating the relationship between CSR and consumer trust. Furthermore, consumer trust strongly predicts entrepreneurial venture performance, highlighting trust as a critical driver of business success in emerging ventures. These findings underscore the strategic importance of integrating CSR initiatives and actively managing brand reputation to foster consumer trust, which in turn improves venture outcomes. The study contributes to both academic literature and practical management by providing a comprehensive model of how responsible practices influence consumer perceptions and entrepreneurial performance